COVID-19 and Mesenchymal Stem Cell Treatment; Mystery or Not - AKKOÇ, TUNÇ (My University, 2020)
On December 31, 2019, novel SARS-CoV2 spread from Wuhan China to more than 200 territories around world and the World Health Organization declared a COVID-19 pandemic on January 30, 2020. At this time there is no particular therapy, drug or vaccine available to deal with COVID-19. Today actual data indicates that about 17% of closed COVID-19 cases died. Health care professionals, ministry of health in countries and the public are trying to read the runes to see when the COVID-19 pandemic will be over. Although mild cases of COVID-19 can be controlled with antiviral, anti-inflammatory and immunomodulatory treatment, severe cases may need intensive care unit support and ventilation. Cytokine storms cause high inflammatory responses and pneumonia in severe cases. Mesenchymal stem cells are immunomodulatory and they have regenerative capacity. In this sense, mesenchymal stem cells may improve the patient's clinical and immunological response to COVID-19.
Keywords: Humans; COVID-19; SARS-CoV-2; Betacoronavirus; Coronavirus Infections; Pandemics; Pneumonia, Viral; Mesenchymal Stem Cells; Mesenchymal stem cells; Cytokine storm; Multiorgan failure; SARS CoV-2